EXAMINATION IN THEORY OF ACCOUNTS. - Zlatkovich, Charles T. (The Accounting Review, 1961)
Abstract This article focuses on the examination in theory of accounts of the Uniform Certified Public Accountants. There were two groups of question. In one of the question one is to indicate the nature of the account or accounts to he debited when recording each transaction using tile preferred accounting treatment by placing an "X" in the proper column on the answer sheet provided. Prepayments should be recorded in balance sheet accounts. Disregard income tax considerations unless instructed otherwise. The question includes facts like, the Talbot Co. spent $8,600 during the year for experimental purposes in connection with the development of its product. This is approximately the same amount that the company has been spending for this purpose annually for many years. The Placey Co. recently purchased land and two buildings for a total cost of $35,000, and entered the purchase on the books. Razing costs of $1,200 were incurred in removing the smaller building, which had an appraised value at acquisition of $6,200, in order to make room for new construction.